Comparison of islet cell function, insulin sensitivity, and incretin axis between Asian-Indians with either impaired fasting glucose or impaired glucose tolerance, and normal healthy controls. (June 2021) - Roy, Ayan; Kamalanathan, Sadishkumar; Sahoo, Jayaprakash; Kar, Sitanshu Sekhar; Naik, Dukhabandhu; Narayanan, Niya; Merugu, Chandhana; Patel, Deepika
Highlights: Beta-cell secretory function is impaired in native Asian Indian prediabetes subjects. Prediabetes subjects have lesser glucagon secretion during mixed meal tolerance test. Both insulin sensitivity and plasma GLP-1 levels are normal in prediabetes subjects. Abstract: Aims: The objective of this study was to compare the islet cell function, insulin sensitivity, and incretin axis between Asian-Indian subjects with either impaired fasting glucose (IFG), or impaired glucose tolerance (IGT), and normal glucose tolerance (NGT). Materials and methods: Prediabetes subjects underwent a mixed meal tolerance test(MMTT) after overnight fasting. Samples for glucose, insulin, glucagon, and glucagon-like peptide-1 (GLP-1) were collected at 0, 30, 60, and 120 min. Insulin secretion sensitivity index -2 (ISSI-2) for beta-cell function and Matsuda index for insulin sensitivity were assessed. Alpha cell function was assessed by measuring the area under the curve (AUC) 0-120 glucagon/AUC0-120 glucose. Results: A total of sixty subjects were recruited with 20 in each group. The beta-cell function represented by ISSI-2 was impaired in prediabetes subjects as compared to NGT group (IFG: 2.09 ± 0.44 vs. NGT: 3.04 ± 0.80, P < 0.0001, and IGT: 2.33 ± 0.59 vs. NGT: 3.04 ± 0.80, P = 0.002). Similarly, AUC0-120 glucagon/AUC0-120 glucose was also lower in prediabetes group as compared to healthy controls (IFG: 0.41(0.54) vs. NGT: 1.07(0.39), P = 0.003 and IGT: 0.57(0.38) vs. NGT: 1.07(0.39), P = 0.001). Conclusion: Asian-Indian prediabetes subjects have reduced beta-cell function with lesser glucagon secretion during MMTT as compared to normal healthy controls.